Setting up a cognitive training service for Egyptian older adults - Hassanin, Hany I.; Tawfik, Heba M.; Zygouris, Stelios; Tsatali, Marianna; Sweed, Hala S.; Tsolaki, Magda (Journal of Alzheimer's disease, 2021)
Background: With greying of nations, dementia becomes a public health priority. The rising dementia prevalence escalates both health care expenses and burden, placing the entire healthcare system and caregivers under huge stress. Cognition-oriented i